Design Thinking Approach in Building a Chatbot for Troubleshooting and Handling Disruption Complaints in Network Services - Lubis, Akhyar; Iskandar, Iskandar; Hardinata, Rio Septian; Lubis, Syahrian (International Conference on Sciences Development and Technology, 2022)
This study explores the application of the Design Thinking approach in building a chatbot for troubleshooting and handling service network disruption complaints. Specifically, the DeepDive method IDEO developed is the main framework in the chatbot creation process.DeepDive, as a methodology that focuses on a deep understanding of user needs and creative problem-solving, allows chatbot creators to design solutions that are highly suitable for unique challenges faced by users in network services. The result is a chatbot capable of effectively handling complaints and providing timely solutions.The research results show that applying IDEO's DeepDive methodology can enhance the efficiency and effectiveness of chatbots in addressing disruption complaints. This significantly contributes to improving network service quality and overall customer satisfaction. This study provides important insights for practitioners and researchers on applying Design Thinking and deep-dive methodology in creating chatbot technology.